Peningkatan Literasi Digital di Kalangan Kelompok Tani di Kampung Pinangan Kabupaten Aceh Tengah - Iskandar; Murthada; Prayetno, Bambang Eko; Lestaria, Evi; Budiman; Sarinauli, Barep; Abidin, Zainal; Yanti, Syafridha; Amrizal (Jurnal Masyarakat Indonesia (Jumas), 2024)
This service was carried out to coffee farmers in Pinangan Village, Central Aceh Regency. This community service activity was carried out on Thursday 7 December 2023. The theme of this community service was Increasing Digital Literacy among Farmer Groups in Pinangan Village, Central Aceh Regency. Digital literacy is important for every element of society, including coffee farmers, in carrying out agricultural activities, from searching for information about agriculture to marketing agricultural products. In this community activity, the subject is a group of farmers in Kampung Pinangan, Kec. Kebayakan, Kab. Central Aceh as many as 40 people. The service method is carried out using the lecture method. It is hoped that the results of this service activity can increase the digital literacy knowledge of farmer groups in Pinangan Village, Central Aceh Regency.